Essential Oil Composition, Total Phenol Compounds and Antioxidant Activity of Hypericum perforatum L. Extract Collected from North of Iran - MR Morshedloo; A Ebadi; MR Fatahi Moghaddam; D Yazdani (Institue of Medicinal Plants, ACECR, 2012)
Background: St. John's Wort (Hypericum perforatum L.), as the most important species of the genus, has been used in traditional medicine for thousands of years. Recently, the plant compounds are used to treat mild and moderate depression around the world.   Objective: This study identified the constituents of essential oil and total phenolic compounds and also antioxidant activity of methanol extract of H. perforatum collected from wildly growing area in the north of Iran (Tonecabon, Mazandaran province) .   Methods: Essential oil was extracted by hydro-distillation of air dried flowering shoots using Clevenger apparatus. The essential oils were analyzed by both gas chromatography (GC) and gas chromatography −mass spectrometry (GC-MS). Total phenolic compounds in the methanol (80%) extract were determined according to the Folin-Ciocalteu reagent using tannic acid as standard. Antioxidant activity of extract was also evaluated by DPPH free radical method.   Results: Monoterpens (25.63%) were found to be the major fraction of the oil and α- Pinene (21.88%) was found to be the most abundant compound, followed by nonane (9.77%), n- octane (9.13%) and dodecanol (6.80%). In addition, the results indicated total phenol content (50 μg gallic acid equivalent/g) and antioxidant activity (34. 37 μg/ml) of methanolic extract. Conclusion: α - Pinene was the major constituent of essential oil of H. perforatum tested sample and its methanol extract contained the high amount of total phenolic compounds and consequently exhibited a considerable antioxidant activity.